Understanding carers’ fall concern and their management of fall risk among older people at home - Seng Giap Marcus Ang; Anthony Paul O’Brien; Amanda Wilson (BMC Geriatrics, 2019)
Abstract Background Many older people (care recipients) experience long-term psychological distress due to the fear of falling again. Falls can affect carers due to concerns about their care recipients falling. Understanding carers’ fall concern is crucial to determine if carers are coping with the provision of care or have adequate knowledge and support in preventing their care recipients from falling at home. Methods A descriptive qualitative study was conducted to explore carers’ concern about their care recipients being at risk of falling and their management of fall risk at home. Twenty-two carers were recruited from two research registers and a large tertiary hospital in a regional centre of Australia. Carers were interviewed face-to-face, or by telephone using a semi-structured interview guide about their fall concern. The data was analysed using an inductive content analysis method. Results Eight major themes emerged from the interviews. Four themes described key factors influencing carers’ fall concern which include: 1) carers’ perception of fall and fall risk, 2) care recipients’ behaviour and attitude towards fall risk, 3) care recipients’ health and function, and 4) care recipients’ living environment. Another four themes described the management of care recipients’ fall risk which include: 5) fall prevention strategies used, 6) risk of preventing falls, 7) support from family and friends, and 8) support from healthcare professionals. Conclusions The findings from this qualitative study provide an insight into the carers’ awareness of fall risk, knowledge, and the availability of support in preventing their care recipients from falling at home. Healthcare professionals are encouraged to include carers and address their fall concern to improve fall prevention programmes for care recipients at risk of falling at home.